Habitat‐ and species‐mediated short‐ and long‐term distributional changes in waterbird abundance linked to variation in European winter weather. Issue 2 (16th November 2018) - Pavón‐Jordán, Diego; Clausen, Preben; Dagys, Mindaugas; Devos, Koen; Encarnaçao, Vitor; Fox, Anthony David; Frost, Teresa; Gaudard, Clemence; Hornman, Menno; Keller, Verena; Langendoen, Tom; Ławicki, Łukasz; et al.
Abstract: Aim: Many species are showing distribution shifts in response to environmental change. We explored (a) the effects of inter‐annual variation in winter weather conditions on non‐breeding distributional abundance of waterbirds exploiting different habitats (deep‐water, shallow water, farmland) and (b) the long‐term shift in the population centroid of these species and investigate its link to changes in weather conditions. Location: Europe. Methods: We fitted generalized additive mixed Models to a large‐scale, 24‐year dataset (1990–2013) describing the winter distributional abundance of 25 waterbird species. We calculated the annual and long‐term (3‐year periods) population centroid of each species and used the winter North Atlantic Oscillation (NAO) index to explain the inter‐annual and long‐term shifts in their location. Results: (a) Year‐to‐year southwestwards shifts in the population centroids of deep‐ and shallow‐water species were linked to negative NAO values. Shallow‐water species shifted northeastwards associated with positive NAO values and the distance shifted increased with increasing NAO. Deep‐water species shifted northeastwards up to zero NAO indices, but showed no further increase at higher NAO values. (b) Deep‐water species showed long‐term northeastwards shifts in distributional abundance throughout the 1990s and the 2000s. Shallow‐water species, on the other hand, shifted northeastwards during the 1990s and early 2000s, but southwestwards thereafter. There were no significant links between the NAO and year‐to‐year movements or long‐term shifts in farmland species' population centroid. Main Conclusions: We provide evidence for a link between both year‐to‐year and long‐term changes in waterbird winter distributional abundances at large geographical scales to short‐ and long‐term changes in winter weather conditions. We also show that species using shallow water, deep‐water and farmland habitats responded differently, especially at high NAO values. As well as important ecological implications, these findings contribute to the development of future conservation measures for these species under current and future climate change.